Towards the Effective Motivation: The Main Results of DoIT3 Study and Recommendations - Raižienė, Saulė; Gabrialavičiūtė, Ingrida; Garckija, Renata (Psichologija, 2022)
The Circumplex perspective on (de)motivating teaching styles based on Self-determination theory is presented in this paper. Based on the findings of the research project “Towards the effective teaching: the evaluation of (de)motivating teaching strategies and their effects on students’ using Circumplex model” (funded by the Research Council of Lithuania under the National Research Programme Welfare Society, Grant No. S-GEV-21-2) recommendations on how to nourish students’ motivational resources and well-being are provided for professionals working in education.